2010
DOI: 10.1111/j.1746-1561.2009.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Individual and School Factors in Physical Activity Patterns of Secondary-Level Spanish Students

Abstract: Physical education programs may benefit adolescents with different physical activity participation preferences regardless of important individual characteristics and broader school factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
3
9
0
1
Order By: Relevance
“…The girls' lower participation in PE classes can contribute to explain the lower levels of global PA observed in this group. A positive experience in the PE classes is positively associated with global participation in PA 21 . Therefore, time optimization and the quality of the PE classes can favor and stimulate PA among adolescents.…”
Section: Discussionmentioning
confidence: 97%
“…The girls' lower participation in PE classes can contribute to explain the lower levels of global PA observed in this group. A positive experience in the PE classes is positively associated with global participation in PA 21 . Therefore, time optimization and the quality of the PE classes can favor and stimulate PA among adolescents.…”
Section: Discussionmentioning
confidence: 97%
“…Moreno and Cervello () discovered that those who participated in physical activity more than three times a week had higher scores in sport competence than those who participated once a week or less. Juan, Bengoechea, Montes and Bush () concluded that more positive self‐perceptions were positively associated with vigorous, moderate and light physical activity levels. For participants in Juan et al .…”
Section: Introduction and Background Literaturementioning
confidence: 99%
“…Los resultados más bajos son característicos de las personas menos activas, mientras que las puntuaciones más altas son indicativas de los individuos más activos. De acuerdo con investigaciones previas realizadas con adolescentes que utilizan esta misma medida (Piéron et al, 2008;Ruiz-Juan et al, 2010) y para representar mejor los patrones de actividad física, la puntuación se utilizó para clasificar a los participantes en actividad vigorosa, moderada, ligera e insuficiente. Para fines analíticos, se crea una variable dicotómica mediante la agrupación de los participantes clasificados como vigorosamente activos y moderadamente activos (alto nivel de actividad físico-deportiva), por un lado, y ligeramente activos e insuficientemente activos (bajo nivel de actividad físico-deportiva), por otro lado.…”
Section: Instrumentosunclassified